The social effects of the usual individuals on electronic games UBG is a Model - سورێن ئەکرەم حەمە نەجم (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This research has two gates, the first gate is dedicated to the theory of the research and it has three chapters. In chapter one, a research problem, a research significance, a research purpose has been written then. In chapter two the concept of (Consequence, Addiction, video game addiction, PUBG) has been defined as well as chapter three is about the reasons and The Influences of video game addiction. The second gate has been dedicated for applied research and it has the community of the Research, the example of the Research, the method of the Research, the Areas of the research and Tools for Gathering Information, Tools statistical of Data analysis as well. Chapter five is about Analysis and Presentation Data, First debate shows Analysis and Presentation Data, Second debate determinations Conclusion, Research results, Research recommendations Research suggestions, Bibliography, Appendix.